Pendidikan Konseling Membimbing Orang Yang Mengalami Penderitaan Dan Kemalangan : Sebab Dan Strategi Membimbing Orang Yang Mengalami Penderitaan - Olis; Nonce Julianti Manafe (JURNAL KADESI, 2023)
The objective of counseling education is to assist individuals in overcoming personal, social, and emotional difficulties. A crucial aspect of this profession is the capacity to counsel and direct individuals who are experiencing suffering and adversity. This article will discuss the causes of distress and misfortune as well as effective guiding strategies. This paper employs a qualitative descriptive research design and a library-based research methodology. This method falls under phenomenology, which is a conceptual study of an individual's personal existence or certain experienced phenomena.